Biogeography of Persephonella in deep-sea hydrothermal vents of the Western Pacific - Mino, Sayaka; Maikita, Hiroko; Toki, Tomohiro; Miyazaki, Junichi; Kato, Shingo; Watanabe, Hiromi; Imachi, Hiroyuki; Watsuji, Tomo-o; Nunoura, Takuro; Kojima, Shigeaki; Sawabe, Tomoo; Takai, Ken; et al. (Frontiers in Microbiology, 2013)
Deep-sea hydrothermal vent fields are areas on the seafloor with high biological productivity fueled by microbial chemosynthesis. Members of the Aquificales genus Persephonella are obligately chemosynthetic bacteria, and appear to be key players in carbon, sulfur, and nitrogen cycles in high temperature habitats at deep-sea vents. Although this group of bacteria has cosmopolitan distribution in deep-sea hydrothermal ecosystem around the world, little is known about their population structure such as intraspecific genomic diversity, distribution pattern, and phenotypic diversity. We developed the multi-locus sequence analysis (MLSA) scheme for their genomic characterization. Sequence variation was determined in five housekeeping genes and one functional gene of 36 P. hydrogeniphila strains originated from the Okinawa Trough and the South Mariana Trough. Although the strains share > 98.7% similarities in 16S rRNA gene sequences, MLSA revealed 35 different sequence types, indicating their extensive genomic diversity. A phylogenetic tree inferred from all concatenated gene sequences revealed the clustering of isolates according to the geographic origin. In addition, the phenotypic clustering pattern inferred from whole-cell matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF/MS) analysis can be correlated to their MLSA clustering pattern. This study represents the first MLSA combined with phenotypic analysis indicative of allopatric speciation of deep-sea hydrothermal vent bacteria.